(untitled) (Research, Society and Development, 2020)
Objective: to know the strengths and weaknesses related to the participation of the father / partner in prenatal care in the perception of Primary Health Care nurses. Method: it is a qualitative research of the descriptive and exploratory type. Semi-structured interviews and Content Analysis were used. Results: 11 nurses participated in this study, who work 40 hours a week in the health service, with an average training time of 15.36 years and the time in the respective units where they work is 3.96 years. The results showed that there are weaknesses for parent / partner adherence in prenatal consultations, involving culture, habits and social conditions. However, when he actively participates in the consultations, he reaffirms the commitment of fatherhood and benefits the care of the pregnant woman and the baby. Conclusion: integration and active participation in consultations offers greater security, confidence and joy in the care of pregnant women. The limitation of the study was the difficulty in finding updated studies related to the theme, which indicates the need for more research on this subject.